(untitled) (Estudios de Historia de España, 2020)
The city of Seville was characterized by fervent animosity in its religious manifestations. Fe and pomposity were confused in the religious festivals and it was what characterized her, coming to rival the institutions among themselves to do the most recognized in Seville capital. The need to make their religiosity felt in the community made the city get accustomed to a notorious public religious manifestation that contrasted with the manifestations of other places, especially those of the north of the Iberian Peninsula